Production of Lipase by Aspergillus fumigatus in Solid State Fermentation Using Residues from Rice - Castiglioni, Gabriel Luis; Costa, Jorge Alberto Vieira (Agrociencia Uruguay, 2015)
Many factors can influence the production of lipase in a fermentation process, among them the air supply and the type of substrate. Biotechnological advances in industrial production of lipase have been allowing the application of this enzyme in different sectors, making it economically viable. This study aimed to evaluate the production of lipase by Aspergillus fumigatus in different nutritional and aeration conditions. The experiments were performed in column bioreactors aerated with 0, 40, 60, 80, 120 and 200 mLair.gmedium-1.h-1, in a medium with no additional carbon source and containing soybean oil and diesel. Significant difference (p <0.05) was observed in the results of lipase activity. The best activities were 103.13, 105.76 and 100.19 U.g-1 using 80 mLair.gmedium-1.h-1 for 48, 72 and 48 h of fermentation, for experiments with no additional carbon source containing soybean oil and diesel, respectively.